(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The integration of capital budgeting techniques with risk management practices is crucial in making informed investment decisions, especially in an uncertain economic environment. This study explores effective integration methods through a systematic literature review approach. By utilizing international databases such as Scopus, Web of Science, and IEEE Xplore, and using the PRISMA method, relevant articles discussing capital budgeting, risk management, and the integration of the two were analyzed. The findings of this study indicate the importance of combining NPV, IRR, and sensitivity methods with risk management to improve the accuracy of investment evaluation. The implications of this research include practical applications for managers and practitioners as well as recommendations for future research.